GUIDELINES FOR POLICY AND STRATEGIC LEADERSHIP MANAGEMENT OF PRIVATE UNIVERSITIES IN GUANGXI PROVINCE, PEOPLE’S REPUBLIC OF CHINA - Gi, Gong; Suteeniran, Niran; Wimuttipanya, Jittawisut; Sittiwiset, Sahasaya (Journal of MCU Nakhondhat, 2023)
The purpose of study on 1) To study policy and strategic leadership management of private universities in Guangxi Province. People's Republic of China 2) To assess the policy and strategic leadership management model of private universities in Guangxi Province, People's Republic of China 3) To study the policy and strategic leadership management approaches of private universities in Guangxi Province. They were selected by purposive sampling method 20 people from each university, totaling 480 people. The interview group was the president or vice president of the university. 1 person per university, totaling 24 people. The group of appraisers for the suitability of the implementation consisted of experts from the university. and those who have main roles in policy and strategic management, totaling 20 people. The data were collected by using 5-point rating scale questionnaire and were statistically analyzed in percentage, mean, and standard deviation. The finding of the study on the study the policy and strategic leadership management approaches of private universities in Guangxi Province, People's Republic of China was at high level. The Strategic Leadership Management was at high level. Executives can transfer knowledge and information appropriately. in operating procedures for transferring knowledge or receiving information is extremely important because it will help the organization move in the right direction.